2014
DOI: 10.1074/jbc.m113.529982
|View full text |Cite
|
Sign up to set email alerts
|

Matrilin-1 Is an Inhibitor of Neovascularization

Abstract: Background:The relative avascularity of cartilage has made it a promising source of angiogenesis inhibitors. Results: MATN-1, identified by mass spectrometry, suppresses capillary endothelial cell proliferation and migration. Conclusion: MATN-1 is a novel inhibitor of neovascularization in vivo and in vitro.Significance: This is the first demonstration that MATN-1 is an inhibitor of both normal and pathological neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…Other authors indirectly observed the basic role of anti‐angiogenic factors involved in development, for example Foradori et al . observed that, in Matrilin‐1‐deficient mice, the angiogenesis during fracture healing was significantly higher in Matrilin‐1−/− mice compared to the wild‐type mice, as demonstrated by elevated expression of angiogenesis markers including PECAM1, VEGFR and VE‐cadherin in that cartilage. When we consider the results of the present study, as a whole, we can observe a clear switch between the expression of SOX9 and COLL II, while the peak level of ENDO corresponded to the intermediate young age.…”
Section: Discussionmentioning
confidence: 95%
“…Other authors indirectly observed the basic role of anti‐angiogenic factors involved in development, for example Foradori et al . observed that, in Matrilin‐1‐deficient mice, the angiogenesis during fracture healing was significantly higher in Matrilin‐1−/− mice compared to the wild‐type mice, as demonstrated by elevated expression of angiogenesis markers including PECAM1, VEGFR and VE‐cadherin in that cartilage. When we consider the results of the present study, as a whole, we can observe a clear switch between the expression of SOX9 and COLL II, while the peak level of ENDO corresponded to the intermediate young age.…”
Section: Discussionmentioning
confidence: 95%
“…We next determined the anti-angiogenic impact of ICAM-Lcn2-LPs using three in vitro angiogenic assays: human endothelial cell proliferation, migration, and tube formation. 23 , 24 , 26 Human microvascular endothelial cells (HMVECs) and human umbilical vein endothelial cells (HUVECs) were chosen as two representative normal human endothelial cell lines. We first examined the effect of ICAM-Lcn2-LP treatment on endothelial cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Endothelial cell proliferation was measured using our previously reported protocol with modifications. 23 , 24 5 × 10 3 human endothelial cells (HMVECs or HUVECs) were plated in each well of a 96-well plate and treated for 48 h with CM harvested from MDA-MB-231 treated with (1) PBS (control), (2) Free Lcn2 siRNA, (3) ICAM-SCR-LP, (4) Lcn2-LIPO, (5) IgG-Lcn2-LP, and (6) ICAM-Lcn2-LP at the final siRNA concentration of 100 nM as described above. The human endothelial cell proliferation was analyzed using a Dojindo cell counting kit using the protocol from the Dojindo Molecular Technologies (Rockville, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation assays were performed as previously described by us (16,(20)(21)(22). In brief, HMVEC-D, HMVEC-L, and HMVEC-M cells transfected with control siRNA or siZNF24 were serum starved overnight and seeded in EGM-2 MV at 5000 cells per well in triplicate in 48-well plates.…”
Section: Proliferation and Apoptosis Assaysmentioning
confidence: 99%